The Neurobiological Basis of the Conundrum of Self-continuity: A Hypothesis - Izadifar, Morteza (Frontiers in Psychology, 2022)
Life, whatsoever it is, is a temporal flux. Everything is doomed to change often apparently beyond our awareness. My body appears totally different now, so does my mind. I have gained new attitudes and new ambitions, and a substantial number of old ones have been discarded. But, I am still the same person in an ongoing manner. Besides, recent neuroscientific and psychological evidence has shown that our conscious perception happens as a series of discrete or bounded instants— it emerges in temporally scattered, gappy, and discrete forms. But, if it is so, how does the brain persevere our self-continuity (or continuity of identity) in this gappy setting? How is it possible that despite moment-to-moment changes in my appearance and mind, I am still feeling that I am that person? How can we tackle with this second by second gap and resurrection in our existence which leads to a foundation of wholeness and continuity of our self? How is continuity of self (collective set of our connected experiences in the vessel of time) that results in a feeling that one’s life has purpose and meaning preserved? To answer these questions, the problem has been comprehended from a psychological and neuroscientific perspective. I realize that first and foremost fact lies in the temporal nature of identity. Having equipped with these thoughts, in this article, it is hypothesized that according to two principles (the principle of reafference (von Holst and Mittelstaedt, 1950) or corollary discharge (Sperry, 1950) and the principle of a time theory) self-continuity is maintained. It is supposed that there should be a precise temporal integration mechanism in the CNS with the outside world that provides us this smooth, ungappy flow of the Self. However, we are often taken for granted the importance of self-continuity, but it can be challenged by life transitions such as entering adulthood, retirement, senility, emigration, and societal changes such as immigration, globalization, and in much unfortunate and extreme cases of mental illnesses such as schizophrenia.